2008
DOI: 10.1210/jc.2007-1784
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Ingestion of Amino Acids and Proteins on the Somatotropic Axis

Abstract: Ingestion of soy protein, either hydrolyzed or intact, as well as AAs reflecting soy protein, stimulates GH release to a similar extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…In our previous work, we found that soy stimulates the GH secretion to a higher extent than a mixture of ARG and LYS, which indicates that also other AAs than ARG and LYS are involved in the GH secretion (van Vught et al, 2008). This result is confirmed by this study, showing that a-lactalbumin and milk also increase the GH response, but in IAUC and peak not different from soy.…”
Section: Somatotropic Effects Of Different Proteins Ajah Van Vught Et Alsupporting
confidence: 87%
See 1 more Smart Citation
“…In our previous work, we found that soy stimulates the GH secretion to a higher extent than a mixture of ARG and LYS, which indicates that also other AAs than ARG and LYS are involved in the GH secretion (van Vught et al, 2008). This result is confirmed by this study, showing that a-lactalbumin and milk also increase the GH response, but in IAUC and peak not different from soy.…”
Section: Somatotropic Effects Of Different Proteins Ajah Van Vught Et Alsupporting
confidence: 87%
“…Especially ingestion of the combination of the AAs arginine (ARG) and lysine (LYS) in a ratio of 1:1 was found to be a potent GH secretor (Isidori et al, 1981). Previously we found that ingestion of soy protein (SOY), containing relatively high amounts of ARG and LYS in approximately equal amounts, stimulates the GH secretion twofold more compared with a mixture of ARG and LYS (van Vught et al, 2008). From this, it can be concluded that besides ARG and LYS, also other AAs stimulate the somatotropic axis, as indeed was shown for the AAs methionine, phenylalanine, histidine, glycine and glutamic acid (Knopf et al, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…GH is an important regulator of growth and body composition. Through GH receptor (GHR) pathway (Kita et al, 2005) GH promotes synthesis and release of IGF-I (insulin-like growth factor 1) (van Vught et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…IV administration of ornithine stimulates GH release as well (Evain-Brion et al 1982). The stimulatory effect of these AA on GH secretion is also evident upon oral administration (Chromiak and Antonio 2002), suggesting a role of dietary AA in the regulation of plasma GH concentrations (van Vught et al 2008;Isidori et al 1981). CAA depletion could also compromise IGF-1 production.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between LPI and GHD was also postulated because of the known interaction between the amino acids (AA) arginine, ornithine, and lysine and GH secretion (Alba-Roth et al 1988;Knopf et al 1965;van Vught et al 2008;Isidori et al 1981).…”
Section: Introductionmentioning
confidence: 99%